An Overview of Some Hydrological Models in Water Resources Engineering Systems - Ibrahim, U. A.; Dan’azumi, S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Researches in hydrological modelling are aimed to the understanding of the behavior of hydrologic systems in an attempt to make better predictions and to address the major challenges in water resources systems. Hydrological modelling concept is concerned with the relationship of water, climate, soil and land use. Hydrological models are classified either as: conceptual or physical, lumped or distributed, deterministic or stochastic. Hydrological models are the main tools that hydrologist use with different purposes such as water resources management, storm water management, reservoir system analysis, flood prediction, climate change assessment and among others. Many hydrological models have been developed for different purposes. The methodology for using hydrological models include: definition of the problem and specifying the objectives, studying the data available, specifying the economic and social constraints, choosing a particular class of hydrological models, selecting a particular type of model from the given class, calibrating and validating the model, evaluating the performance of the model, and finally using the model for the specified purpose. Some recently developed, frequently used, and powerful hydrological models including WEAP, SWMM, HEC-HMS, HEC-RAS, and HEC-ResSim were herein assessed taking into cognizance their applications in solving challenges in water resources engineering systems.